Speech text of symposium on strategy & transformation management for tertiary education (SSTM-TEd 2023) / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
The SSTM-TEd 2023 gathers speakers from universities and various institutions around the world to share their best practices in strategic thinking and transformational management. 5. The symposium aims to provide a platform for the exchange of insights, challenges, and successes in navigating the dynamic landscape of strategic management at the university level.